Intended consequences : birth control, abortion, and the federal government in modern America - Critchlow, Donald T., 1948- (Oxford University Press, 1999)
After World War II, American policy experts - convinced that unchecked population growth threatened global disaster - successfully lobbied bipartisan policy-makers in Washington to initiate federally-funded family planning. In Intended Consequences, Donald T. Critchlow deftly chronicles how the government's involvement in contraception and abortion evolved into one of the most bitter, partisan controversies in American political history. Intended Consequences encompasses over four decades of political history, examining everything from the aftermath of the Republican "moral revolution" during the Reagan and Bush years to the current culture wars concerning unwed motherhood, homosexuality, and the further protection of women's abortion rights. Critchlow's carefully balanced appraisal of federal birth control and abortion policy reveals that despite the controversy, the family planning movement has indeed accomplished much in the way of its intended goal - the reduction of population growth in many parts of the world